Xanthine oxidase inhibitors treatment or discontinuation effects on mortality: evidence of xanthine oxidase inhibitors withdrawal syndrome - Kuwabara, Masanari; Nakai, Michikazu; Sumita, Yoko; Iwanaga, Yoshitaka; Ae, Ryusuke; Kodama, Takahide; Hisatome, Ichiro; Kamatani, Naoyuki (Frontiers in Pharmacology, 2024)
Objectives: This study investigates the impact of xanthine oxidase inhibitors (XOI) on mortality in patients with cardiovascular diseases. XOI withdrawal has been reported to increased mortality risk due to rapid adenosine triphosphate (ATP) deficiency. This study aims to determine whether XOI treatment reduces mortality and whether XOI withdrawal increases mortality. Methods: This is a real-world database study using the Japanese Registry of All Cardiac and Vascular Diseases (J-ROAD). We analyzed 1,648,891 hospitalized patients aged 20-90 with acute coronary syndrome or heart failure. In the first study, mortality rates were compared between patients without urate-lowering agents (n=1,292,486) and those with XOI agents (n=315,388, excluding 41,017 on other urate-lowering agents). In the second study, mortality rates were compared between the XOI continuous medication group (n=226,261) and the XOI withdrawal group (n=89,127). Results: After multiple adjustments, XOI treatment group showed significantly lower mortality compared to the XOI withdrawal group (odds ratio (OR), 0.576, 95% confidence interval (CI), 0.567-0.587, P<.001). In the sub-analysis, the group with allopurinol (OR, 0.578; 95% CI, 0.557-0.600), febuxostat (OR, 0.610; 95% CI, 0.599-0.622), and topiroxostat (HR, 0.545; 95% CI, 0.473-0.628) showed lower OR of mortality compared with that without any urate-lowering agent. XOI withdrawal group led to significantly higher death rates compared to XOI continuous group (19.8% vs. 0.03%; P<.001). Conclusions: XOI treatment for patients with cardiovascular diseases is associated with reduced mortality. Conversely, XOI withdrawal is linked to elevated mortality risk. This emphasizes the importance of both prescribing and discontinuing XOI carefully to optimize patient outcomes.